Ekspeditionen som undersøgelsesmetode - Haahr, Jakob (Forum for Idræt, 2015)
There is a long tradition for going on expeditions. What is special about expeditions as an approach and a method? Which knowledge processes are brought into play? And how can these be used in practice when studying one’s own culture? This is explored by going on smaller expeditions around the Helnæs Bay and the South Funen Archipelago in Denmark. The Nordic outdoor education perspective is used to understand the knowledge processes brought into play.